Sesquin, a potent defensin-like antimicrobial peptide from ground beans with inhibitory activities toward tumor cells and HIV-1 reverse transcriptase - Wong, Jack Ho; Ng, Tzi Bun (Peptides (New York, N.Y. : 1980), 2005)
An antifungal peptide with a molecular mass around 7 kDa and an N-terminal sequence highly homologous to defensin was isolated from ground beans ( Vigna sesquipedalis cv. ‘Ground Bean’). The peptide was adsorbed on Affi-gel blue gel and on Mono S. It exerted an antifungal action on Botrytis cinerea, Fusarium oxysporum and Mycosphaerella arachidicola; and an antibacterial action on Escherichia coli B, Proteus vulgaris, Mycobacterium phlei and Bacillus megaterium. The antimicrobial activity was inhibited in presence of the 5 mM CaCl 2 and MgCl 2, but no inhibition was observed in 5 mM NaCl. The peptide exerted antiproliferative activity toward breast cancer (MCF-7) cells and leukemia M1 cells, this activity could not be inhibited by the ions mentioned above. It also exhibited some inhibitory activity toward human immunodeficiency virus-type 1 reverse transcriptase.